Good Amil Governance in Zakat Management in West Sumatra - Elvira, Rini; Yaswirman, Yaswirman; Effendi, Nursyirwan; Devianto, Dodi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Good Amil Governance is needed in the management of zakat. The performance of zakat management by all BAZNAS in West Sumatra during the 2021-2022 period is still quite good. This performance needs to be improved by paying attention to the application of good amil governance in zakat management. The purpose of this study is to evaluate the extent of the application of good amil governance in zakat management, and the extent to which the relationship can be measured. The research uses a mixed-methods approach. Data collection techniques used documentation, questionnaires, and in-depth interviews. Data sources come from secondary, and primary data. The object of research is all BAZNAS in West Sumatra Province with 193 amil zakat respondents selected by total sampling technique. Qualitative descriptive analysis describes the extent of the implementation of good amil governance in zakat management, and regression analysis measures the relationship between the two. The research findings explain the application of good amil governance in the management of zakat in all BAZNAS in West Sumatra is quite good with a value of 0.42 (42%). Both have a positive influence relationship with a value of 45.7%, and the rest is influenced by other variables such as the availability of financial resources, the level of technology use, the level of muzzaki trust in zakat institutions, and local cultural values. This research provides an understanding of the importance of implementing good amil governance in zakat management to achieve goals.